Hubungan Jenjang Pendidikan dan Pengalaman Kerja dengan Produktivitas - Sari, Andi Ratna (Patria Artha Management Journal, 2023)
This study aims to determine whether the level of education and work experience affect employee performance at PT Indah Logistik Cargo Cabang Makassar. The analytical method used is the research instrument test (validity and reliability test), data analysis techniques (multiple regression equations and descriptive analysis), hypothesis testing (coefficient of determination (R²), simultaneous F test and partial t test), and classical assumption test (normality test, multicollinearity test, and heteroscedasticity test). The results showed that the level of education had a positive and significant effect on employee performance and work experience had a positive and significant effect on employee performance, while simultaneously the level of education and work experience had a positive and significant effect on employee performance.